Mitigation strategies to safely conduct HIV treatment research in the context of COVID‐19. Issue 2 (9th February 2022) - Henderson, Merle; Fidler, Sarah; Mothe, Beatriz; Grinsztejn, Beatriz; Haire, Bridget; Collins, Simon; Lau, Jillian S. Y.; Luba, Maureen; Sanne, Ian; Tatoud, Roger; Deeks, Steve; Lewin, Sharon R.
Abstract: Introduction: The International AIDS Society convened a multidisciplinary committee of experts in December 2020 to provide guidance and key considerations for the safe and ethical management of clinical trials involving people living with HIV (PLWH) during the SARS‐CoV‐2 pandemic. This consultation did not discuss guidance for the design of prevention studies for people at risk of HIV acquisition, nor for the programmatic delivery of antiretroviral therapy (ART). Discussion: There is strong ambition to continue with HIV research from both PLWH and the research community despite the ongoing SARS‐CoV‐2 pandemic. How to do this safely and justly remains a critical debate. The SARS‐CoV‐2 pandemic continues to be highly dynamic. It is expected that with the emergence of effective SARS‐CoV‐2 prevention and treatment strategies, the risk to PLWH in clinical trials will decline over time. However, with the emergence of more contagious and potentially pathogenic SARS‐CoV‐2 variants, the effectiveness of current prevention and treatment strategies may be compromised. Uncertainty exists about how equally SARS‐CoV‐2 prevention and treatment strategies will be available globally, particularly for marginalized populations, many of whom are at high risk of reduced access to ART and/or HIV disease progression. All of these factors must be taken into account when deciding on the feasibility and safety of developing and implementing HIV research. Conclusions: It can be assumed for the foreseeable future that SARS‐CoV‐2 will persist and continue to pose challenges to conducting clinical research in PLWH. Guidelines regarding how best to implement HIV treatment studies will evolve accordingly. The risks and benefits of performing an HIV clinical trial must be carefully evaluated in the local context on an ongoing basis. With this document, we hope to provide a broad guidance that should remain viable and relevant even as the nature of the pandemic continues to develop.